Danone Indonesia’s B Corp Certification and Its Impact on Sustainable Business Practices - Karyanto Wibowo; Pradhipto Bagas Wicaksono (Journal of Research on Business and Tourism, 2025)
The Fast-Moving Consumer Goods (FMCG) sector in Indonesia faces significant challenges in adopting sustainable practices amidst environmental issues like water scarcity and plastic waste, compounded by social and regulatory complexities. This study explores how Danone Indonesia’s B Corp certification, achieved in 2018, drives transformative sustainability in its operations. Using a qualitative case study approach, the research analyzes secondary data from company reports, B Corp assessments, and industry sources, focusing on CO2 emission reduction, water stewardship, circular economy initiatives, and employee engagement. Findings reveal that certification catalyzed measurable improvements, including a CO2 reduction roadmap, 50% reduction in water usage, 25% recycling rate for PET bottles, and a 95% employee engagement score, aligning with global sustainability standards. These outcomes demonstrate that B Corp certification can inspire systemic change in emerging markets, offering a model for balancing profit with purpose in Indonesia’s dynamic business landscape.